Predators, livestock losses and poison in the South African Karoo - Nattrass, Nicoli; Conradie, Beatrice (Journal of cleaner production, 2018)
A panel study of 66 sheep farmers in the South African Karoo, in the years 2012, 2013 and 2014, revealed that farmers cull predators (black-backed jackals, caracals and baboons) in response to livestock losses. Those whose entire livelihood came from sheep farming culled predators in greater numbers. Killing predators, however, is probably counter-productive as culling is associated with greater livestock losses the following year. This finding is robust to the inclusion of a set of socio-economic and farm-level characteristics and is consistent with predator ecology (killing territorial predators can create vacancies for dispersing juveniles to move in to, resulting in greater stock losses later). Farmers also reported that both lethal and non-lethal methods to control predators were becoming less effective over time. This is in line with evidence highlighting the capacity of caracals and especially black-backed jackals to adapt to persecution. Poison use is widespread and unrelated to socio-economic status. Reported poison use increased over the study period. Poison has unintended effects on wildlife (killing non-target animals, especially scavenger species) and poses challenges for cleaner production and sustainable development. [Display omitted] •South African sheep farmers cull predators (black-backed jackals, caracals and baboons) in response to livestock losses.•Culling predators is associated with greater livestock losses the following year, indicating lethal control is probably counter-productive.•Farmers report that lethal and non-lethal methods to control predators are becoming less effective over time.•Poison use is widespread, unrelated to socio-economic status, and probably on the increase.•This is damaging to wildlife and poses challenges for cleaner production and sustainable development.